PENGARUH JENIS PAKAN BUATAN DAN ALAMI TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP LARVA UDANG VANAME (Litopenaeus vannamei) - Tiara Putri; Supono Supono; Berta Putri (Universitas Sriwijaya, 2020)
The study aimed to determine how the growth and survival capabilities of vaname shrimp larvae (Litopenaeus vannamei) are affected by different feeding methods and thereby the most efficient method. The study was conducted at the PT. Citra Larva Cemerlang, South of Kalianda in Lampung Province. For the experiment Completely Randomized Design (CRD) was utilized with 3 feeding methods and each was replicated 3 times. The feeding methods tested were: fozen, liquid and powdered Artemia feed. The experiments were done with up to 5000 shrimps on Zoea 1 stadia per month, which were kept in rearing tanks for 17 days.The test parameters observed were absolute growth, specific growth rate, efficiency of feed utilization, survival rate and water quality. Based on the results of statistical analysis (Anova) feeding frozen Artemia gave the best results with absolute growth of 5,6 mg, daily growth rate of 0,33 mg/hari, efficiency of feed utilization of 0,27%, and survival rate of 72,9%. Water quality during maintenance temperatures obtained is 27,1-32oC, pH 7,73-8,26, dissolved oxygen 3,8-7,1 mg/l, salinity 30-34 ppt, ammonia 0,02-1,57 mg/l. Keywords: Litopenaeus vannamei, Artemia, growth, frozen, powder, liquid.